CONCURRENT DIABETES MELLITUS AND RENAL INSUFFICIENCY AS PROGNOSTIC INDICATORS FOR ACUTE MYOCARDIAL INFARCTION: A COHORT STUDY. - Singh, Brajesh Kumar (Student’s Journal of Health Research Africa, 2024)
Background Acute myocardial infarction (AMI) prognosis worsens with diabetes mellitus and renal failure. This study examines how the combined presence of these comorbidities affects clinical outcomes in AMI patients. Methods 100 people with AMI participated in this cohort study, which ran from September 2023 to August 2024. Based on whether or not they had diabetes mellitus and renal insufficiency, participants were divided into four groups. To account for potential confounders, multivariate regression analysis, ANOVA, chi-square tests, and descriptive statistics were used to examine clinical outcomes. Results The study included 100 AMI patients with a mean age of 64 years, predominantly male (64%) but with a substantial female representation (36%). Common comorbidities such as smoking, hypertension, and hyperlipidaemia were consistently observed across all groups. The patients in Group IV, who had both kidney failure and diabetes, had the highest incidence of MACE (56.2%) and the longest hospital stay (7.9 ± 3.2 days), and also the highest rate of mortality in hospital (26.8%). Both renal failure (Odds Ratio 3.2, 95% Confidence Interval 2.1-4.9) and diabetes mellitus (Odds Ratio 2.4, 95% Confidence Interval 1.6-3.6) were found to be significant independent predictors of unfavourable outcomes using multivariate regression analysis. Conclusion Following an AMI, patients with concurrent diabetes mellitus and kidney failure have far worse outcomes than those with either condition alone or neither. These results highlight the necessity of close observation and specialized treatment plans for this high-risk group. Recommendations For AMI patients who also have diabetes and renal failure, healthcare practitioners should use integrated care approaches. To enhance outcomes for these patients, further research should concentrate on creating and assessing targeted therapies.